AN INVESTIGATION ON THE IMPACT OF PHYSICAL ENVIRONMENT ON THE FORMATION AND CONTINUITY OF ANCIENT SETTLEMENTS, CASE STUDY THE MEREK RIVER CATCHMENT, CENTRAL ZAGROS, IRAN - Mohsen Heydari Dastenaei; Kamal Adin Niknami (Journal of Ancient History and Archaeology)
The geographical environment, especially its natural bed, is the area of all actions and reactions resulting from phenomena located on the surface of the earth. The natural environment is the most important factor in the formation of human settlements, especially in different periods. Factors such as altitude, slope, geological structure, faults, water resources, soil, vegetation and land use are natural substrates affecting the distribution of human settlements. The present study aims to investigate the relationship between the formation and continuity of ancient settlements and their environmental bed in the Merek River catchment. To achieve the objectives of the research, 6 natural criteria were considered environmental factors or independent variables, and the area of ancient sites was regarded as a dependent variable. To investigate these factors, Arc Gis and SPSS software programs and inferential statistics quantitative analysis with the Pearson correlation method were used. Additionally, multiple linear Regression was used to investigate the effect of several independent variables on the dependent variable. The results indicate that the areas of the Merek River catchment are directly related to natural factors such as altitude, distance from rivers, and distance from communication routes and type of land use, and a number of other environmental factors are slightly associated with ancient sites. They have caused the people of the past in this region to choose two types of livelihood for their lives.